Granular biodurable nanomaterials: No convincing evidence for systemic toxicity. (November 2014) - Moreno-Horn, Marcus; Gebel, Thomas
Abstract Nanomaterials are usually defined by primary particle diameters ranging from 1 to 100 nm. The scope of this review is an evaluation of experimental animal studies dealing with the systemic levels and putative systemic effects induced by nanoparticles which can be characterized as being granular biodurable particles without known specific toxicity (GBP). Relevant examples of such materials comprise nanosized titanium dioxide (TiO2) and carbon black. The question was raised whether GBP nanomaterials systemically accumulate and may possess a relevant systemic toxicity. With few exceptions, the 56 publications reviewed were not performed using established standard protocols, for example, OECD guidelines but used non-standard study designs. The studies including kinetic investigations indicated that GBP nanomaterials were absorbed and systemically distributed to rather low portions only. There was no valid indication that GPB nanomaterials possess novel toxicological hazard properties. In addition, no convincing evidence for a relevant specific systemic toxicity of GBP nanomaterials could be identified. The minority of the papers reviewed (15/56) investigated both nanosized and microsized GBP materials in parallel. A relevant different translocation of GBP nanomaterials in contrast to GBP micromaterials was not observed in these studies. There was no evidence that GPB nanomaterials possess toxicological properties other than their micromaterial counterparts.